ANALISIS KEPUASAN SATUAN KERJA PERANGKAT DAERAH (SKPD) DAN REKANAN TERHADAP KINERJA UNIT LAYANAN PENGADAAN (ULP) PEMERINTAH KABUPATEN BADUNG - Budayasa, Putu; Salain, I M.Alit K; Nadiasa, Mayun (JURNAL SPEKTRAN; Vol 4 No 1 (2016): Vol. 4, No. 1, Januari 2016DO - 10.24843/SPEKTRAN.2016.v04.i01.p04)
Abstract: Based on Presidential Decree Number 54 Year 2010 concerning Government Procurement of Goods / Services. Procurement process carried out by a unit called the Procurement Service Unit (PSU). In Government of Badung Regency, PSU was formed in 2011wich often get a negative presumption of those associated with the Unit is the Regional Work Unit and Partner Company when carry out the procurement process. Under these conditions it is necessary to evaluate the services given. The research aimed to determine the level of satisfaction Regional Work Unit and Partner Company of the performance of the Procurement Unit of Badung Regency and to investigate the influence of the five dimensions of service quality and satisfaction levels  wich is Tangible, Reliability, Responsiveness, Assurance and Empathy. Sampling using simple random sampling with a sample of 30 of Regional Work Unit and 71 of the Partner Company. Measuring the level of satisfaction is done by comparing the scores of hope with a score of respondents' perceptions of reality services received. While to know the factors that influence satisfaction of Partner company and regional work unit done by searching multiple linear regression model. The analysis was conducted to determine the effect or the relationship between variables, either partially or simultaneously. The results of descriptive analysis expressed Regional Work Unit satisfaction level is 86.28%, which factors most influence satisfaction is Assurance. Partner Company satisfaction level is 86.4% which factors most influence satisfaction is Tangible. Results inferential analysis states that the fifth dimension is influenced simultaneously and partially on both Regional Work Unit and Partner Company satisfaction .
Keywords: Procurement Unit, Satisfaction, Procurement of Goods / Services